Understanding how intermediaries connect adults to community-based physical activity: A qualitative study - Megan O’Grady; Emer Barrett; Deirdre Connolly (PLoS ONE, 2025)
Intermediaries facilitate connections to community-based services and supports, including physical activity and exercise groups, and are an emerging method to promote physical activity participation. However, their processes when establishing connections to community-based physical activities are unclear. The aim of this study was to explore the processes, practices, and procedures of Irish intermediaries when connecting people to community-based physical activity. This was a qualitative descriptive design study. Semi-structured interviews were carried out with n = 27 intermediaries from a variety of sectors—Health Promotion and Improvement [HPO], Local Sports Partnerships [LSO] and Social Prescribing [SP]. Four themes were identified using qualitative content analysis; 1) the processes of connecting to an intermediary, 2) connecting individuals to physical activity, 3) exiting from the intermediary service and 4) working in the local context. Intermediaries reported that they received referrals for individuals with physical, mental, and social health needs, but that referrals to improve physical activity specifically were low. They used a person-centred approach throughout their process, often addressing barriers to physical activity. However, only LSO and SP facilitated connections to physical activity, as HPO mainly focused on delivering smoking cessation support and services. Levels of support given and length of follow-up varied between LSO and SP, with the latter providing more intensive support. To facilitate their work, they developed extensive local knowledge and networks of partners, which enabled connections to a variety of community-based physical activities. Intermediaries may be an under-utilized resource to promote physical activity. Understanding the processes used in their interventions can inform future research, which is needed to investigate the effectiveness of intermediaries in improving physical activity levels and to inform future referral pathways.